The Long Journey of the Icononaut - Brunetta, Gian (Cinémas, 1992)
This article attempts to establish a preliminary topology and to formulate a few hypotheses based on research into the mechanisms, forms, sites andcultural and iconographie configurations that led to the birth of the Icononaut, the Visionary, the traveller in the iconosphere. Having carried out research in the 1980s into the spread and characteristics of the image industry and market from the seventeenth to the nineteenth centuries, including travelling and folk representations and the constitution of a lexicon of popular images, the author aims to show how this immense system, unifying and transforming the mental "geography" of millions in Europe and elsewhere, can be seen as the habitat and birthplace of cinematic representations.